Cruise Business Development Safety, Product Design and Human Capital - Papathanassis, Alexis (Springer International Publishing : Imprint: Springer, 2016)
This book addresses innovation management and product development in the cruise tourism industry. It explains how experience management has evolved from a strictly company-level, product- or service-focused tactical task to an industry-wide strategic challenge, and analyses the role of intangible reputational aspects of cruise experiences, as well as peripheral components and stakeholders, as increasingly important factors for customer acquisition and retention. Safety and risk issues are a central theme, as well as the cruise sector's environmental and socio-economic impacts. Lastly, the book considers the increasing size of cruise vessels and the accompanying standardisation of facilities and itineraries, in conjunction with the hybridisation of cruise passengers in connection with expanding the competitive boundaries and intensity of competition in the cruise sector. The book approaches these issues as more than a mere public relations campaign, recognising the fact that they have since become the very essence of strategic cruise business development.